2013
DOI: 10.1177/0300060513504358
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the toll-like receptor 2 and 4 genes are associated with faster progression and a more severe course of sepsis in critically ill patients

Abstract: Two common SNPs of the TLR2 and TLR4 genes--Arg753Gln and Asp299Gly--were associated with a shorter time-to-onset of severe sepsis or septic shock in patients admitted to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
(43 reference statements)
0
19
0
11
Order By: Relevance
“…TLR2 is expressed not only in immune cells, but is also present in pulmonary alveoli and airway epithelial cells, suggesting that it plays a role in mucosal innate immunity and infection-induced lung injury (Charles et al, 2011; Hertz et al, 2003; Hoth et al, 2012; Jiang et al, 2005). Interestingly, TLR2 deficient mice are highly susceptible to S. aureus infection (Takeuchi et al, 2000), and in humans, a loss-of-function TLR2 mutation has been linked to susceptibility to infectious and inflammatory diseases, faster disease progression, and a more severe course of sepsis in critically ill patients (Bronkhorst et al, 2013; Janardhanan et al, 2013; Nachtigall et al, 2014; Stappers et al, 2014). These studies illustrate the protective role of TLR2 in response to inflammatory insults and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…TLR2 is expressed not only in immune cells, but is also present in pulmonary alveoli and airway epithelial cells, suggesting that it plays a role in mucosal innate immunity and infection-induced lung injury (Charles et al, 2011; Hertz et al, 2003; Hoth et al, 2012; Jiang et al, 2005). Interestingly, TLR2 deficient mice are highly susceptible to S. aureus infection (Takeuchi et al, 2000), and in humans, a loss-of-function TLR2 mutation has been linked to susceptibility to infectious and inflammatory diseases, faster disease progression, and a more severe course of sepsis in critically ill patients (Bronkhorst et al, 2013; Janardhanan et al, 2013; Nachtigall et al, 2014; Stappers et al, 2014). These studies illustrate the protective role of TLR2 in response to inflammatory insults and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some of the gene polymorphisms (GPs) influencing normal immune system function have been studied to analyze if giving prophylactic antibiotics to a group with susceptibility is more efficient. This has been done in cancer patients in a limited number of groups (Dahmer et al, 2005;Nachtigal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study by Nachtigall et al . reported that the polymorphism rs4986790 might shorten the time-to-onset of severe sepsis or septic shock in patients permitted to intensive care units45. In the study by Child et al ., the polymorphism rs4986790 was demonstrated to be involved in the severity of SIRS46.…”
Section: Discussionmentioning
confidence: 95%